DISCOVERING THE CHALLENGES AND OBSTACLE OF MALAYSIAN SINGLE MOTHER ENTREPRENEURS - Rosfatihah Che Mat,; Ahmad Firdause Md Fadzil,; Suraya Hussin,; Sakinah Mat Zin,; Khamisah Abdul Manaf,; W. Nurfahizul Ifwah W. Alias, (Journal of Islamic, Social, Economics and Development, 2023)
Research on women's entrepreneurship has captured the attention of academics ever since a significant number of women participate actively in various business activities. The current research, on the other hand, is insufficient to provide a complete explanation of the challenges and obstacle encountered by women entrepreneurs because there are still gaps in the data especially for single mother entrepreneurs. The literature on the challenges and obstacle faced by women entrepreneurs is analysed. Several studies related to single mother entrepreneurs is then being discussed to reach conclusion on how these women entrepreneurs identify the challenges and confront the situation. The result revealed that challenges like economic, psychological factors, political environment, balancing between home and business, insufficient support and social stigma were among significant problems found effecting the success of single mother entrepreneurs. These obstacles should be encountered as quickly as possible so that single mother entrepreneurs can be successful in their business field. The focus is to assist these women entrepreneurs particularly single mothers’ entrepreneurs to participate in entrepreneurial activities and survive without relying solely to the government assistant or support. Thus, this paper review shows an opportunity for academics to conduct research in women entrepreneurship development particularly using single mother entrepreneurs as the subject of study.